Synthesis and Characterization of Two New Asymmetrical Potentially Heptadentate (N4O3) Tripodal Schiff Base Ligands and a Theoretical Study - Salehzadeh, Sadegh; Mahnaz Nouri, Seyedeh; Keypour, Hassan (Asian Journal of Chemistry, 2010)
Two new asymmetrical potentially heptadentate N4O3 Schiff-base ligands {[NCH2CH2CH2N = CH(2-OH-3, 5-t-Bu2C6H2)]-[ CH2CH2CH2N = CH(2-OH-C6H4)]2} (H3L1) and {N[CH2CH2- CH2N = CH(2-OH-C6H4) [CH2CH2CH2N = CH(2-OH-3, 5-t-Bu2-C6H2)]2} (H3L2) were synthesized and characterized by microanalysis and various spectroscopic methods (IR, 1H NMR and 13C NMR). The heptadentate N4O3 Schiff-base ligand H3L1 was derived from the condensation reaction of tripodal tetraamine ligand tris(3-aminopropyl)amine with 2 equiv. of salicylaldehyde and 1 equiv. of 3,5-di-t-butyl salicylaldehyde and the ligand H3L2 was derived from the condensation reaction of tris(3-aminopropyl)amine with 1 equiv. of salicylaldehyde and 2 equiv. of 3,5-di-t-butyl salicylaldehyde. The relative capability of these ligands to encapsulation of a lanthanide ion, herein La(III), has been theoretically studied by ab initio restricted Hartree-Fock (RHF) and DFT (B3LYP) methods. The calculation confirmed that these ligands can effectively encapsulate a lanthanide ion and enforce a sevencoordinate geometry.